Financial performance evaluation of Islamic banking system : a comparative study among Malaysia’s banks - Samsudin Hazman; Nawawi Mohd Nasir; Abd Halim Zairihan; Md Said Ahmad Syahmi (Penerbit Universiti Kebangsaan Malaysia, 2018)
The promotion of Islamic banking is parallel with the aim of Malaysia to be the pioneer of Islamic financial hub in the region. With the recent commitment, it is timely to further examine the performance of the industry constituents. Therefore, this study aims to investigate the performance of Islamic banking system in comparison to its conventional counterpart in Malaysia using CAMEL model. For that purpose, annual financial data collected from ten conventional and Islamic banks in Malaysia since 2004 until 2016 is used in the analysis. Both Dynamic Ordinary Least Square (DOLS) and Fully Modified Ordinary Least Square (FMOLS) estimations technique as suggested by Pedroni (2001) are employed. We find that conventional banking system performed better than its counterpart. The maturity of conventional banks which has treads Malaysia’s financial market earlier could plausibly dominate the results. Our evidence suggests that the regulators should strengthen Islamic banking system through more reforms and mergers to improve its capital, assets, management, earnings and liquidity.